Strategi Pembelajaran Guru dalam Memenuhi Kebutuhan Belajar Peserta Didik Ditengah Pandemi Covid-19 Di SD Negeri 66 Gantarang Kabupaten Sinjai - Miftakul Khoiri (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2021)
Currently, the world is faced with problems that affect all sectors including education with the covid-19 outbreak. So the teacher has extra work so that the educational process runs optimally by using several teaching methods that are by current conditions. The purpose of this study is to analyze the extent to which the efforts or roles of teachers in meeting the learning needs of students. In the learning process that is carried out outside the classroom, it is intended that all the needs of students, such as academic, psychological, and comfortable needs can be met. The method in this study used a data-based qualitative descriptive method. The author analyzes the needs of students in the learning process amid the Covid-19 pandemic and the learning strategies used by teachers in meeting the learning needs of students. Researchers analyzed how the strategies used by teachers at SD Negeri 66 Gantarang in meeting the learning needs of participants so that the learning needs of students could be met.